Fast-Food Consumption Patterns among University Students: A Case Study of McDonald's in Malaysia - Odebunmi Abayomi Tunde; Thiam Yong Kuek; Nitin Mohan; Gautam Rastogi; Gunjan Bhatt; Hershita Singh; Mar'atus Sholikhah; Vaisnave A/P Murugesan; Venishya A/P Ganeson; Yoke Jing Wong; Chiam Yeu Yap; Aisyah Wardina; Binti Mohamed Hassan; Daisy Mui Hung Kee (AIBPM Publisher, 2023)
In contemporary times, the accelerated pace of life has brought about a noticeable alteration in the lifestyle of human beings. One of the most discernible changes is the amplified reliance on fast food among individuals, with university students being particularly susceptible to this trend. The objective of this research paper is to address the matter of McDonald’s fast-food consumption patterns among university students in Malaysia. This study aims to establish the relationship between the independent variables of taste, prices, convenience, advertisement, and eating habits, and the dependent variable of McDonald’s fast-food consumption patterns among university students. A total of 150 university students in Malaysia participated in an online survey through a Google Form. The results indicate that taste, prices, convenience, advertisements, and eating habits significantly influence McDonald’s fast-food consumption patterns among university students in Malaysia. Recommendations and consequences were discussed.